Antígona como figura arquetípica do herói de tragédia conforme Aristóteles - Barcelos, Regina Célia (2023)
This research was outlined with the aim of comparing characteristics of Sophocles' protagonist, Antigone, with the most outstanding attributes of the hero of the tragedy described by Aristotle, especially in his Poetics. This work has a merely exploratory character and was developed from certain historical, cultural, mythical-religious and artistic data, based on works by distinguished researchers of themes that deal with the context in which Antigone was brought to light by the poet's hands. Interweaving Sophocles' text and Aristotle's writings demands efforts to understand what was the context of the time, what was the public and how it is possible to apprehend the particularities of the Theban princess in her trajectory as the heroine of the tragedy. In Antigone's verses, we can capture certain specificities of the character, contrasting her words with others, her posture in the search for good and correct behavior in the face of contempt for timeless human values. The research started with the purpose of highlighting the traits that establish Antigone as a notable example of a hero of Greek tragedy.